Determinants of edtech success: an empirical analysis of dynamic capabilities and key facilitators - Silva, Rosemeire; Noronha, Matheus; Ferraro, Diandra Maynne Juliano (Review of Artificial Intelligence in Education, 2023)
Objective: This research aimed to evaluate whether factors such as longevity, investments, number of employees, and location serve as facilitators in promoting the success of educational technology companies (edtechs), and if they aid in enhancing dynamic capabilities. Method: The theoretical lens employed for this study is centered around dynamic capabilities and success criteria. Data was extracted from Crunchbase, a platform encompassing commercial and financial data on companies, and was complemented by an exploration of academic literature using the Scopus database. This holistic approach aimed at mapping academic interest around the topic. Two software tools were employed: Jasp for variance analysis (ANOVA) and VosViewer for keyword co-occurrence analysis in data investigation. Results: Statistical analyses underpin the theoretical foundation and offer evidence suggesting that Crunchbase can provide crucial information to gauge the success of edtechs. This information can bolster investment decisions and further support the academic field with updated data on edtech establishments. Conclusions: The set objective of identifying elements that might contribute to an edtech's success was achieved. Data from Crunchbase was scrutinized, buttressed by a descriptive graphical analysis. To supplement this, Scopus-based literature was reviewed to provide an encompassing perspective. Practical Implications: Understanding these identified success factors can guide potential investors and entrepreneurs in making informed decisions in the edtech industry, potentially leading to more innovative and successful educational technology models in the market.